Topology of 2D turbulent structures based on intermittence in the TJ-II stellarator. (14th October 2021) - van Milligen, B.Ph.; Melnikov, A.V.; Carreras, B.A.; García, L.; Kozachek, A.S.; Hidalgo, C.; de Pablos, J.L.; Khabanov, P.O.; Eliseev, L.G.; Drabinskiy, M.A.; Chmyga, A.; Krupnik, L.; et al.
Abstract: This work estimates the degree of turbulent intermittence of the plasma potential measured by a heavy ion beam probe in the core plasma region of the TJ-II stellarator. It is shown that the intermittence varies in a significant way with the plasma state (ion or electron root). In addition, radial minima of the intermittence are found to be associated with the location of topological structures of the flow associated with some important low-order rational surfaces. The local pressure gradient was also estimated, and a clear correlation was found between the steepening of the pressure gradient and the deepening of the minima of the intermittence, suggesting that the minima are associated with pressure gradient driven modes. By estimating the rotation velocity of the plasma from the measured plasma potential, it was possible to make a rough reconstruction of the two-dimensional radial–poloidal map of intermittence, thus clarifying the topological structure of the intermittence. The experimental results were put into context by comparing with simulations performed using a resistive magneto-hydrodynamic turbulence model.